The clinical utility of microsatellite instability in colorectal cancer - Diao, Zhenli; Han, Yanxi; Chen, Yuqing; Zhang, Rui; Li, Jinming (Critical Reviews in Oncology/Hematology, 2021)
[Display omitted] Microsatellite instability (MSI) became the spotlight after the US FDA’ s approval of MSI as an indication of immunotherapy for cancer patients. Immunohistochemical detection of loss of MMR proteins and PCR amplification of specific microsatellite repeats are widely used in clinical practice. Next-generation sequencing is a promising tool for identifying MSI patients. Circulating tumour DNA provides a convenient alternative when tumour tissue is unavailable. MSI detection is an effective tool to screen for Lynch syndrome. Early-stage CRC patients with MSI generally have a better prognosis and a reduced response to chemotherapy; instead, they are more likely to respond to immunotherapy. In this review, we aimed to assess the clinical utility of MSI as a biomarker in CRC. We will provide an overview of the available methods for evaluation of the analytical validity of MSI detection and elaborate the evidence on the clinical validity of MSI in the management of CRC patients.